Manufacturing of Transparent MgAl2O4 Ceramics by Spark Plasma Sintering Combined with Collector Pressing Method - Paygin V. D. Vladimir Denisovich; Dvilis E. S. Edgar Sergeevich; Deulina D. E. Darjya Evgenjevna; Stepanov S. A. Sergey Aleksandrovich; Khasanov O. L. Oleg Leonidovich; Valiev D. T. Damir Talgatovich; Shevchenko I. N. Ivan Nikolaevich; Huang Fuli (2025, 2025)
Title screen